Preparation and Properties of Composite PAN/PANI Membranes. (8th February 2017) - Fryczkowska, Beata; Piprek, Zofia; Sieradzka, Marta; Fryczkowski, Ryszard; Janicki, Jarosław
Abstract : The methods of modifying PAN membranes have been known and used for many years. An interesting solution seems to be to give the sensory properties to this type of membranes. This paper presents the results of research on the method of obtaining PAN/PANI membranes using phase inversion method from a solution in DMF, following two methods: (1 ) dissolving both polymers (PAN and PANI) and then coagulating in water or in an aqueous solution of CSA and (2 ) forming the membranes from polyacrylonitrile solution and coagulation in water, followed by coating of CSA with a solution of TFE. The membranes obtained as a result of the experiment were tested for physical and chemical properties, transport properties, surface morphology, degree of dispersion of composite components, and sensitivity to the presence of dilute acids and bases. FTIR microspectroscopy and scanning electron microscopy were used to study the surface morphology. The sensory properties of membranes that are inherently colored were determined visually and by UV-Vis spectrophotometry. Furthermore, when choosing the method of membrane forming, we can obtain membranes with good physical and chemical and transport properties or ones characterized by high sensitivity to the pH of the solution.